Sphenoidal emissary foramen and its clinical consideration - Jadhav, Surekha D.; Ambali, Manoj P.; Zambare, Balbhim R. (International Journal of Research in Medical Sciences, 2017)
Background:Sphenoidal emissary foramen is a small, variable and an inconstant foramen in middle cranial fossa which is located antero-medial to the foramen ovale. Emissary vein passing through it connects the pterygoid venous plexus with the cavernous sinus which has clinical significance because through an extra-cranial infection may reach to cavernous sinus. Aim of present study was to investigate the incidence and shape of sphenoidal emissary foramen, the number of present on one side and the presence of bony septum in it. Methods: Two hundred and fifty (right 250; left-250) dry Indian adult skulls of unknown age and sex were used for this study. Middle cranial fossa of each skull was macroscopically observed for the presence, absence of sphenoidal emissary foramen. Patency was confirmed by inserting a bristle through each probable foramen and only patent foramen were calculated. Results: We observed that sphenoidal emissary foramen was present in 72 (28.8%) skulls. Unilaterally it was present in 17.6% and bilaterally in 11.2% skulls. Conclusions: Incidence of this foramen is variable and therefore recognition of this anatomical structure is important. Knowledge of their variations will be helpful for neurosurgeons and radiologist.